Swim that rock - Rocco, John (Candlewick Press, 2014)
When his dad goes missing in a fishing-boat accident, fourteen-year-old Jake refuses to think he may have lost his father forever. But suddenly, nothing seems certain in Jake's future, and now his family's diner may be repossessed by loan sharks. In Narragansett Bay, scrabbling out a living as a quahogger isn't easy, but with the help of some local clammers, Jake is determined to work hard and earn enough money to ensure his family's security and save the diner in time.